Survey on Tunisian Dentists’ Anti-Inflammatory Drugs’ Prescription in Dental Practice - Line Berhouma; Amira Besbes; Abdellatif Chokri; Jamil Selmi (The Scientific World Journal)
Dentists prescribe several types of drugs such as anti-inflammatory medicines in their practice in order to manage pain. An adequate knowledge of anti-inflammatory drugs’ characteristics is mandatory for a reasonable prescription to ensure patients safety. The study aimed to describe dentists’ anti-inflammatory drugs prescription in dental practice. Materials and Methods. This study was conducted on independent practice dentists working in the region of Tunis. A questionnaire was made on “Google forms” and sent to all of them via personal emails. The questionnaire included demographic data and 13 questions about anti-inflammatory medicines: indications and contraindications, the side effects, and their prescription in dental practice. Data analysis was performed on SPSS software version 20.0 (trial version), using the χ2 test for statistical analysis. Results. Two hundred dentists participated to the survey. The female gender was predominant (70%). More than half of the responders were recently graduated and working in their own dental offices. The present study showed that 60% of dentists rarely prescribe anti-inflammatory drugs. Ibuprofen was prescribed by 82% of the dentists. Next came dexamethasone acetate (68.2%). The most frequent indication was postoperative pain (65%). Gastric problem was found to be the most mentioned adverse effect (69%). Thus, 72% of the dentists prescribed proton pump inhibitors with AI. Conclusion. According to this study, dentists have a lack of knowledge and awareness about some contraindications, side effects, and drugs interactions. Thus, knowledge updating, practices assessment, and continuous education are always required to avoid drug iatrogenesis.